Rural women’s behavior in preserving environmental resources in some villages of Beheira Governorate in the Arab Republic of Egypt - Ebaid, Hanan Ibraheem; Harhash, Ebtsam Zagloul Mohamed; Ibrahim, Eman Mostafa (Journal of agricultural, environmental and veterinary sciences, 2022)
This research study aims to assess the level of knowledge, attitudes, and implementation of correct practices related to environmental resource preservation, as well as to identify the reasons for not implementing these practices. The study was conducted in Beheira Governorate due to the increased percentage of water pollution above the acceptable limit and the average rates of air pollution. Following that, three centers were chosen, namely Damanhour, Kom Hamada, and Itai Al- Baroud, and a village was selected from each center, namely Azab Al- Serw, Al- Shabur, and Kafr Musaed, respectively. The sample size was determined using a simple fraction, with 471 samples distributed in the same proportion as each village’s representation within the total sample size. Rural women participants were randomly chosen from a total of 4, 709 agricultural landowners’ wives. The village Azab Al- Serw had 136 respondents, and the eastern village of Shabur had 213 respondents, while 122 surveyed in the village of Kafr Musaed. Data were collected during November and December of 2021 using a personal interview questionnaire. Data were analyzed and expressed using frequencies, percentages, mean, standard deviation, t- test, and correlation coefficients. The most noticeable results were: - 69.9 % of women included in the present study have a medium to low level of knowledge of correct practices in environmental resource preservation, and more than half of participants 53.9 % have a neutral attitude, while 87.5 % have implemented correct practices in this field. - Among the reasons for not implementing these correct practices are a 94.5 % lack of conviction in the feasibility of implementing environmental resource conservation practices, a 92.8 % lack of information about the importance of preserving environmental resources for rural women and their families, and 4.90% were accustomed to wrong practices in dealing with environmental resources.